Engineering of composite metallic microfibers towards development of plasmonic devices for sensing applications. Issue 1 (January 2016) - Petropoulou, A; Antonopoulos, G; Bastock, P; Craig, C; Kakarantzas, G; Hewak, D W; Zervas, M N; Riziotis, C
Abstract: The paper discusses the analysis of tapered hybrid composite microfibers based on a metal-core and dielectric-cladding composite material system. Its advantages over the pure metal tips conventionally used, are the inherent enhanced environmental robustness due to inert borosilicate cladding and the capability of multiple excitation of the tapered nanowire through the length of the fiber due to the enabled total internal reflection at the borosilicate/air interface. Simulations through finite element method (FEM) have demonstrated an improved field enhancement at the tapered region of such microfibers. Furthermore, experimental results on tapering in copper based microfibers together with light coupling and propagation studies will be demonstrated revealing the potential for the development of plasmonic devices for sensing applications.